Production and Characterization of Gelatine Based Electro-spun Nano-fibres as Burn Wound Dressings - Y. Hamedani; N. Fazeli; J. Barzin (Iranian Journal of Chemical Engineering)
Silver sulfadiazine is used to prevent and treat infections of second- and third-degree burns. It kills a wide variety of bacteria. In this study silver sulfadiazine was used in gelatin based electro-spun nano-fibers with various drug to polymer ratios (0, 5, 10, 15 and 20 %). SEM, EDX and FTIR analysis showed that the continuous, bead-free, fine fibers containing silver sulfadiazine as an antibiotic drug were successfully produced. The release profiles of the loaded drug from the produced nano-fibrous dressings were evaluated by an in vitro elution method. It was observed that the sample with 10wt% of gelatin has had the optimum trend of release. Moreover, antibacterial activity of the dressings was evaluated against the pathogenic micro-organisms S.aureus and E.coli in the nutrient agar solid medium. It was obvious that all the samples had antibacterial activity against these two bacteria. The produced silver sulfadiazine loaded gelatin based electro-spun nano-fibrous dressings have the potential for being used in the wound healing applications.